Continuous Glucose Monitoring–Enhanced eConsult Improves Clinical Outcomes in Adults Living With Diabetes in a Safety Net Primary Care Setting - Samantha M. Siskind; Ryanne Dymek; Kathryn L. Fantasia; Katelyn O’Brien; Devin W. Steenkamp (Journal of Diabetes Research)
Conclusion: In adults living with diabetes cared for in a safety-net hospital, CGM-enhanced eConsult provides timely access to endocrinologist expertise, recommendations are widely implemented by primary care clinicians, and guideline-directed modern diabetes therapeutic use increases, including a 17-fold increase in personal CGM prescriptions.